2013
DOI: 10.1128/cvi.00325-12
|View full text |Cite
|
Sign up to set email alerts
|

Additional Diagnostic Yield of Adding Serology to PCR in Diagnosing Viral Acute Respiratory Infections in Kenyan Patients 5 Years of Age and Older

Abstract: The role of serology in the setting of PCR-based diagnosis of acute respiratory infections (ARIs) is unclear. We found that acuteand convalescent-phase paired-sample serologic testing increased the diagnostic yield of naso/oropharyngeal swabs for influenza virus, respiratory syncytial virus (RSV), human metapneumovirus, adenovirus, and parainfluenza viruses beyond PCR by 0.4% to 10.7%. Although still limited for clinical use, serology, along with PCR, can maximize etiologic diagnosis in epidemiologic studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 17 publications
(19 reference statements)
1
21
0
Order By: Relevance
“…The proportion of diagnostic seroresponses was higher for all patients with high virus loads (lower C T values), which would be predicted for primary virus infections and is consistent with case-control studies that have shown higher virus loads among RT-PCR-positive symptomatic patients than among matched asymptomatic controls (9,16,21). The relative prevalences of virus detection and patterns of age distribution found in this study were similar for RT-PCR and serology and were consistent with those reported in other CAP studies (9,10,19). Finally, for most viruses, positive test results obtained by both methods were temporally concordant with each other and with the seasonal circulation patterns of the respective respiratory viruses described by regional NREVSS data over the study period.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The proportion of diagnostic seroresponses was higher for all patients with high virus loads (lower C T values), which would be predicted for primary virus infections and is consistent with case-control studies that have shown higher virus loads among RT-PCR-positive symptomatic patients than among matched asymptomatic controls (9,16,21). The relative prevalences of virus detection and patterns of age distribution found in this study were similar for RT-PCR and serology and were consistent with those reported in other CAP studies (9,10,19). Finally, for most viruses, positive test results obtained by both methods were temporally concordant with each other and with the seasonal circulation patterns of the respective respiratory viruses described by regional NREVSS data over the study period.…”
Section: Discussionsupporting
confidence: 91%
“…Molecular studies of respiratory virus infections that have included serology have generally increased the number of acute infections identified (12,19,20). However, the added diagnostic value of serology for the etiologic assessment of CAP in U.S. populations has not been fully evaluated.…”
mentioning
confidence: 99%
“…Serologic testing for select viruses (AdV, HMPV, influenza A and B, PIV, and RSV) was performed on available paired acute and convalescent serum specimens. Influenza serology used both hemagglutination inhibition and microneutralization assays to define positive results [14, 15], and serology for other viruses was based on CDC-developed indirect immunoglobulin (Ig)G enzyme immunoassays [11, 12]. Bacterial culture was performed on specimens from blood, sputum, pleural fluid, endotracheal aspirates, and bronchoalveolar lavage.…”
Section: Methodsmentioning
confidence: 99%
“…Real-time polymerase chain reaction (PCR) assays are most commonly performed on respiratory specimens in etiology studies, because they have improved sensitivity and turnaround time for respiratory virus detection relative to culture [6–10]. Although not timely, serology may capture infections even if a virus is not sufficiently present to be detected by PCR in respiratory specimens; thus, acute and convalescent (paired sera) serology results can increase the diagnostic yield for respiratory viruses in CAP studies [3, 4, 11–13]. However, even in the research setting, paired sera are not always available from each patient, particularly because convalescent serology requires specimen collection posthospital discharge or death.…”
mentioning
confidence: 99%
“…Acute-and convalescent-phase serology paired with PCR increases the diagnostic yield of RSV, in patients 5 years of age and older, from 8.3% with PCR alone to 11.3% with acute-and convalescent-phase serology (210). Enzyme immunoassays (EIAs) against envelope glycoproteins have a sensitivity greater than HEp-2 tube culture.…”
Section: Rsv Serology Serologic Testingmentioning
confidence: 99%